The Impact Of Tolerance on Self-Regulation in Kinderganten Children: An Ex Post Facto Investigation - Era Pratiwi Mazly; Amir Syamsudin (International Journal of Education and Teaching Zone, 2025)
This quantitative study employs an ex post facto design to investigate the predictive relationship between tolerance and self-regulation in early childhood (N = 99; ages 4–6 years). Participants were purposively sampled from Tabir District, Indonesia, to represent the key socioeconomic and cultural characteristics of the region. Validated instruments measuring tolerance (α=0.793) and self-regulation (α=0.799) demonstrated robust psychometric properties through content validity testing and Cronbach’s Alpha reliability analysis. Linear regression analysis (SPSS v.28) revealed tolerance as a statistically significant predictor of self-regulation (β = 0.398, p < 0.001, 95% CI [0.291, 0.505]), accounting for 15.8% of the variance (R² = 0.158). Crucially, we identify a novel mechanistic pathway: tolerance not only enhances behavioral regulation but also significantly contributes to social-emotional competencies within learning contexts (b = 0.427, SE = 0.098, p < 0.001). These findings advance the Social Learning Theory framework by demonstrating how prosocial dispositions scaffold regulatory development. We propose empirically testable models for tolerance-based interventions to optimize early childhood developmental trajectories.